Increasing Students' Ability on Maintaining the School Cleaning Environment Through Morning-Based Activities of Modelling Technique for Retarded Students - Youlanda Agustin; Armaini (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This study aims to determine the ability of children to maintain the cleanliness of the school environment in the sweeping aspect of middle-aged children in Perwari Padang Special School. This research is to find out whether training based modelling technique is effective in improving children’s ability to maintain the cleanliness of the school environment in middle-aged children. The type of research method used by SSR is using A-B-A design. The test used is an action test; the researcher instructs the child to imitate and practice. After analyzing baseline acquisition data (A1) the ability of the child is still low, the in condition (B) the child is given treatment in this condition the child’s ability to maintain environmental hygiene significantly increases. At baseline (A2) observations were made after treatment was given through an exercise-based modelling technique, the child’s ability was good. From these result, exercise-based modelling techniques can improve children’s ability to maintain the cleanliness of the school environment in sweeping aspects